Inbreeding and inbreeding depression in endangered red wolves (Canis rufus). Issue 17 (21st August 2014) - Brzeski, Kristin E.; Rabon, David R.; Chamberlain, Michael J.; Waits, Lisette P.; Taylor, Sabrina S.
Abstract In natural populations, the expression and severity of inbreeding depression can vary widely across taxa. Describing processes that influence the extent of inbreeding and inbreeding depression aid in our understanding of the evolutionary history of mating systems such as cooperative breeding and nonrandom mate selection. Such findings also help shape wildlife conservation theory because inbreeding depression reduces the viability of small populations. We evaluated the extent of inbreeding and inbreeding depression in a small, re‐introduced population of red wolves (Canis rufus) in North Carolina. Since red wolves were first re‐introduced in 1987, pedigree inbreeding coefficients (f) increased considerably and almost every wild born wolf was inbred (average f = 0.154 and max f = 0.383). The large inbreeding coefficients were due to both background relatedness associated with few founders and numerous close relative matings. Inbreeding depression was most evident for adult body size and generally absent for direct fitness measures such as reproductive success and survival; no lethal equivalents (LE = 0.00) were detected in juvenile survival. The lack of strong inbreeding depression in direct measures of fitness could be due to a founder effect or because there were no outbred individuals for comparison. Our results highlight the variable expression of inbreeding depression across traits and the need to measure a number of different traits when evaluating inbreeding depression in a wild population.